Possible effect of IGFR1 gene on macrocephaly in a patient with unbalanced 6;15 translocation with 6p25 deletion and 15q26 duplication - Yararbas, K.; Sayar, C.; Tumer, S.; Ozciger, D.; Tavukcu, C.; Oncu, N.; Alanay, Y. (NATURE PUBLISHING GROUP, 2019)
51st Conference of the European-Society-of-Human-Genetics (ESHG) in conjunction with the European Meeting on Psychosocial Aspects of Genetics (EMPAG), Milan, ITALY, JUN 16-19, 2018